The Influence of Creative Accounting to the Formation of the Accounting Policy and Accounting’s Results - Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2019)
The accounting's policy choice and creating is influenced by accounting theory, impact factors, each company's objectives, and this makes company unique. Legislation for businesses in creating accounting policies allow to choose the following accounting methods and techniques that are most revealing aspects of the activities of the enterprise. In cases where the situation is not exactly to regulate the law is left to creativity. There is a need to apply creative accounting, which is identified as a factor influencing the choice of accounting policy. Taking into account the environmental factors of the company, creative accounting is applying in different accounting areas and in different volumes, while the accounting policy structure is forming. The main source of information about the company's financial position and the results are financial statements. On financial statements basis, information users make decisions. In order to influence information users decision's, company starts to manipulate financial data. In order to influence consumer decisions, creative accounting is used to manipulate financial data, which results in higher or lower company profits and distorts other financial information. On misleading data basis made financial statements not reflect a true and fair view of the company. The size of the distortion of information's, investigations are not carried out In Lithuania. The purpose of the study is analysis of the relationship of creative accounting and accounting policy and determinate the creative accounting impact to the formation of the accounting policy and accounting's results. Methods of analysis, data systematization, comparative, grouping and modeling were used during the research.JEL classification: M41
Keywords: creative accounting; accounting policy; the financial statements